Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 13 (4) The Diseases of Poverty. The relative incidence of certain diseases as between Classes 1 and 2, the professional class, and Class 5, the unskilled and semi-skilled workers is shown in the following table :— Males aged 35-65 Married Women aged 35-65. Illness. Classes 1 & 2. Class 5. Classes 1 & 2. Class 5. Bronchitis 157 53 136 53 Pneumonia 141 79 130 78 Pleurisy 120 83 115 91 Tuberculosis 130 70 133 69 Gastric Ulcer 125 73 ... ... Cancer 114 91 105 97 Syphilis, etc. 136 68 148 52 All classes — 100 (i) Tuberculosis is a disease bred of damp and malnutrition. In 1921-1923 a special survey by the Registrar-General showed that mortality from tuberculosis among the poor was approximately three times as great as among the well-to-do. Its victims pass it on to their brothers and sisters, who must share the same crowded room or bed ; sun and air which are part of its cure, never reach the dark hovels in which so many of its sufferers live. Mr. Rowntree found that in York, out of 125 cases surveyed in which illness was the chief cause of poverty, tuberculosis was responsible for one-seventh. Here is a typical case from his survey : a widow aged 62, living with a daughter of 21 and a son of 17. "They live in a house with three bedrooms, but it is very damp and is subject to flooding when the River Foss overflows. Several children have died from tuberculosis. The widow has had her name down for a Corporation house for five years, but has not yet been able to secure one." In 1928 the Medical Officer of Hull reported that of 539 notified cases of tuberculosis, 134 of the sufferers had not even a separate bed of their own, and 34 were sharing a bed with two or more still healthy persons.* (ii) Rickets are one of the most common consequences of malnutrition among children. Dr. McGonigle found that in County Durham, out of 2,676 children examined, 2,221, or 83 per cent. were definitely rickety and a further 294, or 11 per cent., slightly rickety.† In 1927, a special investigation revealed that out of 1,638 London children examined, 88 per cent. were rickety, three-quarters of them seriously so. There were districts in which less than 9 per cent. of the children were free from the disease.‡ * Condition of Britain, p.106. † Ibid., p. 108. ‡ Ibid., p. 109. 15X/2/98/13